Making Applications for Midwives' Independent Practice Using the Waterfall Method - Azhar, Zainullah (PT. Riset Press International, 2023)
The patient's medical records at the Independent Midwife Practice (PMB) must be stored and kept confidential in order to provide good, quality, and responsive health services to patients. Nuning Midwife Independent Practice Nuning, S.ST,. Tanah Bumbu was founded in 2012. During its 11 years of existence, patients still have to queue in the waiting room for a long time. This is because the service process and medical records used are still manual. This study aims to make a special application on PMB. Researchers use the research and development method to facilitate the research process and the waterfall method as a reference for the PMB application development process. The resulting development product is a PMB application that can provide convenience to midwives in providing services to patients and reduce the long queue of patients in the waiting room. Data collection used interviews with 2 respondents from PMB owners and midwives. The results of the research are in the form of functional and non-functional system requirements for PMB applications. These needs are translated in the form of system design in the form of system flowcharts, use case diagrams, class diagrams, activity diagrams, entity relationship diagrams, and data flow diagrams. The design is then translated into a programming language using PHP programming and MySQL database. From the results of this study, it has several features, namely login features, patient visit report features, patient referral letter features, detailed identity data features for patients and midwives, notification features, patient registration/registration features independently, and patient examination results record features. Features that are not yet available in the PMB application are the automatic payment feature and the distance between the PMB and the referred hospital.